Airway Management for Endoscopic Laryngotracheal Stenosis Surgery During COVID‐19. (12th May 2020) - Prince, Andrew D. P.; Cloyd, Benjamin H.; Hogikyan, Norman D.; Schechtman, Samuel A.; Kupfer, Robbi A.
Abstract : The novel coronavirus disease 2019 (COVID‐19) pandemic presents unique challenges for surgical management of laryngotracheal stenosis. High viral concentrations in the upper aerodigestive tract, the ability of the virus to be transmitted by asymptomatic carriers and through aerosols, and the need for open airway access during laryngotracheal surgery create a high‐risk situation for airway surgeons, anesthesiologists, and operating room personnel. While some surgical cases of laryngotracheal stenosis may be deferred, patients with significant airway obstruction or progressing symptoms often require urgent surgical intervention. We present best practices from our institutional experience for surgical management of laryngotracheal stenosis during this pandemic, including preoperative triage, intraoperative airway management, and personal protective measures.